Hukum Uang Panai’ (Studi Komparasi Antara Fikih Munakahat dan Fatwa Majelis Ulama Indonesia Sulawesi Selatan Nomor 2 Tahun 2022) - Muhammad Istiqamah; Muhammad Muhammad; Muhammad Ikhsan; Ibrahim S. (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research aims to determine the comparison of munākaḥāt jurisprudence and Fatwa MUI Sul-Sel No. 2 of 2022 concerning panai money'. The research method used is descriptive qualitative (non-statistical) with library research methods (literature review) which are processed through normative and comparative approaches. The results of this research found that Panai’ according to the South Sulawesi MUI Fatwa Number 2 of 2022 is permissible or permissible with several provisions. In the perspective of munākaḥāt jurisprudence, panai’ is termed as assets required by the bride's father from the groom, both from the dowry and outside the dowry. From this we can understand the difference between the South Sulawesi MUI Fatwa and the perspective of munākaḥāt jurisprudence, namely in terms of legal understanding and results. And this research further strengthens the opinion of munākaḥāt jurisprudence that it is religious or even haram.